Laser-Sintering of Cyclic Olefine Copolymer for Low Dielectric Loss Applications - Romeis, Manuel; Ehrngruber, Michael; Drummer, Dietmar (Polymers, 2024)
With increasing demands for data transfer, the production of components with low dielectric loss is crucial for the development of advanced antennas, which are needed to meet the requirements of next-generation communication technologies. This study investigates the impact of a variation in energy density on the part properties of a low-loss cyclic olefin copolymer (COC) in the SLS process as a way to manufacture complex low-dielectric-loss structures. Through a systematic variation in the laser energy, its impact on the part density, geometric accuracy, surface quality, and dielectric properties of the fabricated parts is assessed. This study demonstrates notable improvements in material handling and the quality of the manufactured parts while also identifying areas for further enhancement, particularly in mitigating thermo-oxidative aging. This research not only underscores the potential of COC in the realm of additive manufacturing but also sets the stage for future studies aimed at optimizing process parameters and enhancing material formulations to overcome current limitations.
CRIS-Team Scopus Importer:2024-07-12
Keywords: additive manufacturing; COC; cyclic olefine copolymer; low dielectric loss; selective laser sintering; SLS